3D printed PCL/GelMA biphasic scaffold boosts cartilage regeneration using co-culture of mesenchymal stem cells and chondrocytes: In vivo study. (15th November 2021) - Cao, Yanyan; Cheng, Peng; Sang, Shengbo; Xiang, Chuan; An, Yang; Wei, Xiaochun; Yan, Yayun; Li, Pengcui
Graphical abstract: Highlights: A biphasic scaffold consisting of a cells-encapsulated biodegradable gelatin methacrylate (GelMA) hydrogel on the upper layer and a 3D printed poly(ε-caprolactone) (PCL) scaffold filled with cells-encapsulated GelMA hydrogel on the lower layer was fabricated to support cartilage regeneration using co-culture of bone marrow mesenchyml stem cells (BMSCs) and costal chondrocytes (CChon). The synergistic effect of BMSCs and costal chondrocytes was sufficient to induce chondrogenesis, but cartilage regeneration was better under TGF-β3 supplement. The PCL/GelMA biphasic scaffolds with cells co-culture possessed excellent cartilage regenerative capability, and enabled the Young's modulus of engineered cartilage comparable to that of native cartilage. The implantation of biphasic scaffold resulted in less mechanical pain than cartilage defects by gait analysis. Abstract: Cartilage injury is difficult to self-repair, which poses a challenge to scaffold design and selection of seeded cells for cartilage tissue engineering. In this study, we presented a biphasic scaffold consisting of a cells-encapsulated biodegradable gelatin methacrylate (GelMA) hydrogel on the upper layer and a macroporous poly(ε-caprolactone) (PCL) scaffold filled with cells-encapsulated GelMA hydrogel on the lower layer to support cartilage regeneration using co-culture of bone marrow mesenchyml stem cells (BMSCs) and costal chondrocytes (CChon). We determined that the synergistic effect of BMSCs and costal chondrocytes was sufficient to induce chondrogenesis, but cartilage regeneration was better under TGF-β3 supplement. Memorably, when implanted in a rat osteochondral defect model for 12 weeks, the PCL/GelMA biphasic scaffolds with cells co-culture showed excellent cartilage regenerative capability, and enabled the Young's modulus of engineered cartilage comparable to that of native cartilage. Furthermore, the implantation of biphasic scaffold resulted in less mechanical pain than cartilage defects by gait analysis. Together, both in vitro and in vivo results demonstrated that the PCL/GelMA biphasic scaffold with co-culture of BMSCs and chondrocytes is a promising scaffold for cartilage regeneration, which pave a new way to solve the key issues of clinical cartilage repair.